2013
DOI: 10.9790/3013-0311035-40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prenatal Isotretinoin on Postnatal Development of Cornea and Lens in Albino Wistar Rat: A Morphometric and Histopathlogical Analysis

Abstract: Isotretinoin is a known teratogen affecting the neuronal differentiation in developing brain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Inappropriately, retinoids are extremely teratogenic in humans, equal in the therapeutic dosage Even though the mechanism of action of Isotretinoin leading to the droplet in fur of the treated group is static unclear but it is identified that like other retinoids, isotretinoin works by DNA transcription shifting. [9], this effect declines the dimension and production of sebaceous off into the sebaceous glands, creates the cells that are sloughed off into the sebaceous glands fewer sticky, and hence less capable to form comedones. A loss in the weight of the maternal after gestation related to the weight before gestation and control group could be an indicator of drop in the appetite and ill health which essential have been produced by the release of free radicals [10], also related Science, 2017, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriately, retinoids are extremely teratogenic in humans, equal in the therapeutic dosage Even though the mechanism of action of Isotretinoin leading to the droplet in fur of the treated group is static unclear but it is identified that like other retinoids, isotretinoin works by DNA transcription shifting. [9], this effect declines the dimension and production of sebaceous off into the sebaceous glands, creates the cells that are sloughed off into the sebaceous glands fewer sticky, and hence less capable to form comedones. A loss in the weight of the maternal after gestation related to the weight before gestation and control group could be an indicator of drop in the appetite and ill health which essential have been produced by the release of free radicals [10], also related Science, 2017, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Taking isotretinoin 30 d before and during pregnancy has been reported to cause fetal or neonatal problems (above 16 w of gestation), such as fetal death in the uterus, congenital birth defects, and neural tube defects. Congenital anomalies include abnormalities of the skin, abdominal wall, cardiovascular, digestive, nervous, musculoskeletal, respiratory, and urogenital system, as well as multiple chromosomal anomalies/ syndromes and other congenital malformations [41,42].…”
Section: Side Effects and Monitoringmentioning
confidence: 99%